DPMD Communication Strategy to Improve the Performance of Village Of-ficials in Enrekang Regency - Zain, Sukmawati; Unde, Andi Alimuddin; Akbar, Muhammad (LEGAL BRIEF, 2024)
The limited quality and performance of village officials is one of the sources of problems that arise in the Village Government in managing village funds. The research was conducted with the aim of exploring and describing the communication strategy applied by DPMD as a village monitor and coach in an effort to improve the performance of village officials in Enrekang Regency, especially in the management of village funds. Researchers used a qualitative approach with a case study method. The informants taken were four people who had information and experience related to improving the performance of village officials, namely the head of DPMD, the Head of the Division that handled the performance improvement of village officials and 2 (two) Village Heads. In this study, it is known that the communication strategy applied by DPMD in an effort to improve the performance of village officials, especially in the management of village funds, is through several steps, namely by conducting research, planning, implementing and evaluating communication. The communication strategy implemented is quite good, but not optimal because in determining communicants in the implementation of training and socialization, DPMD has not been able to present or invite all village officials who should participate in the process of managing village funds. This is also due to the limited budget of the Enrekang Regency PMD Office